Planning Sludge Bioconversion Using Black Soldier Fly Larvae in Tofu Production Centers - Budi Prasetyo Samadikun; Sri Sumiyati; Bimastyaji Surya Ramadan; Lutfiana Anisa; Chintya Putri Agustin; Irfan Tawakkal (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
Sugihmanik Village, Tanggungharjo District, Grobogan Province, is a major tofu-producing area affiliated with 20 MSMEs and the Waste Transportation Authority (PLTA). Although tofu contributes to the local economy, poor wastewater management from fish farming installations can cause environmental issues. The objective of this study was to develop an environmentally friendly and sustainable wastewater management system based on black solid fuel (BSF). The research methodology included water consumption levels and quality, steam generation, and the development of a BSF bioconversion system. The test results showed that the hydroelectric power plant produced 694.21 kg/day (0.68 m3/day) from the wastewater treatment process. The proposed model utilizes the transition of wastewater and the wastewater environment in the BSF ecosystem. This process produces valuable products, including soft BSF larvae as a protein source and BSF waste as raw material